The criminal costs of wrongful convictions - Norris, Robert J. (Criminology & public policy, 2020)
Research In this article, we examine criminal offending by true perpetrators after innocent people are arrested and convicted for their crimes. After investigating a set of cases in which DNA was used to exonerate the innocent and to identify the guilty party, we identified 109 true perpetrators, 102 of whom committed additional crimes. We found a total of 337 additional offenses committed by the true perpetrators, including 43 homicide-related and 94 sex offenses. By extrapolating from our findings, we estimate that the wrong-person wrongful convictions that occur annually may lead to more than 41,000 additional crimes. Policy Implications Our findings indicate that one consequence of wrongful convictions, allowing the true perpetrators of crimes to remain at liberty and commit new crimes that imperil prospective victims, represents an important threat to public safety and thereby dramatically compounds the harms caused to innocents. We stress the importance of framing wrongful conviction issues to capture these important crime control concerns and, thus, to help galvanize public opinion and promote policy reforms that will mutually benefit adherents of both crime control and due process perspectives.